Energy-storage-efficient 0.9Pb(Mg1/3Nb2/3)O3–0.1PbTiO3 thick films integrated directly onto stainless steel. (December 2021) - Sadl, Matej; Condurache, Oana; Bencan, Andreja; Dragomir, Mirela; Prah, Uros; Malic, Barbara; Deluca, Marco; Eckstein, Udo; Hausmann, Daniel; Khansur, Neamul H.; Webber, Kyle G.; Ursic, Hana
Abstract: The integration of functional ceramics with metals remains challenging due to the thermally activated processes and the incompatibilities that arise during the high-temperature ceramic sintering process. In order to overcome this, low-temperature processing methods can be employed. In this work, dense 0.9Pb(Mg1/3 Nb2/3 )O3 –0.1PbTiO3 thick films were deposited on low-cost, stainless-steel substrates at room temperature using an aerosol-deposition method. The key material parameters for a successful aerosol deposition of the powder were identified and used in the process, which resulted in homogeneous 15-µm-thick films. The as-deposited films can withstand electric fields of 900 kV⋅cm −1 and exhibit promising room-temperature energy-storage properties: the recoverable energy density reaches 7.0 J⋅cm −3 with an energy-storage efficiency of ∼70%. A post-deposition stress relaxation by annealing at 500°C further improves the recoverable energy density, leading to 9.8 J⋅cm −3 at 900 kV⋅cm −1 with an energy-storage efficiency of ∼80%. The energy-storage performance exhibits excellent temperature stability up to 200°C and an electric-field cycling stability up to 16 million cycles. The low-temperature integration of energy-storage-efficient thick films onto stainless steel opens up possibilities for numerous new, pulsed-power and power-conditioning electronic applications. Graphical abstract: Image, graphical abstract